Acute type A aortic dissection repair in younger patients. Issue 4 (13th March 2018) - Uehara, Kyokun; Matsuda, Hitoshi; Matsuo, Jiro; Inoue, Yosuke; Omura, Atsushi; Seike, Yoshimasa; Sasaki, Hiroaki; Kobayashi, Junjiro
Abstract: Aim: To evaluate the surgical outcomes and midterm results of patients under 50 years old with acute type A aortic dissection (AAAD). Methods: The study population included 51 patients who underwent AAAD repair between 2003 and 2016. Of these 51 patients, 46 (90.1%) were males and 14 (27.5%) had connective tissue disorders. Twenty‐five patients (49.0%) had a body mass index >25.0 kg/m 2 and two patients were pregnant. Total arch replacement was performed in 39 patients (76.5%) and hemiarch replacement in 12 patients (23.5%). Twenty patients (39.2%) underwent concomitant surgeries, including root replacement, lower limb bypass, or coronary artery bypass grafting. Results: There was one in‐hospital death (2.0%). Median follow‐up was 55 months and overall survival rates were 87.7% at 5 years and 81.9% at 10 years. Rates of freedom from reoperation were 60.2% at 5 years and 50.2% at 10 years. Eighteen patients (35.3%) required reoperation, due to progressive aortic dilatation, new dissection in the aortic root, infection, and hemolysis. A patent false lumen represented a significant risk factor for reoperation ( P < 0.001). Four patients (7.8%) underwent reoperation within 3 months after the initial repair. Conclusions: Surgical outcomes after AAAD repair for young patients were satisfactory. A patent false lumen significantly increased the need for reoperation ( P = 0.002), but did not affect long‐term survival. Close follow‐up is mandatory after the initial repair in young patients following AAAD.